Pengaruh Kualitas Pelayanan Koperasi Tani Dewi Sri dan Produktivitas Kerja Petani terhadap Kesejahteraan Petani Di Subak Sengempel, Desa Bongkasa, Kecamatan Abiansemal, Kabupaten Badung - Wilantara, I Made Agus; Suamba, Ketut; Adi Putra, I Gede Setiawan (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management), 2017)
ABSTRACT The Influence of Service Quality of Dewi Sri Farmer’s Cooperative and the Farmer’s Work Productivity on the Welfare of Farmer’s at the Subak of Sengempel, Bongkasa Village, Sub-District of Abiansemal, Badung Regency Farmer’s cooperative as a facilitator in improving welfare, the quality of service would be an important part in order to always be the selection of farmers to obtain the required product. The farmer’s cooperative is expected to provide the best services in order to achieve the welfare of farmers. An improved labor productivity of farmers as a source of income will have implications for the welfare of farmers. The study objective was to determine the effect of service quality of the farmer’s cooperative on the welfare of farmers at Subak of Sengempel. The research method used descriptive qualitative method. Total respondents was 151 members of farmer’s cooperative taken by proportional random sampling. Data were analyzed using inferential statistics (SEM-PLS). The results showed that the quality of service of the farmer’s cooperative and the farmer’s work productivity positively and very significantly effect on the welfare of farmers. Quality of services of the farmer’s cooperative positively and very significantly effect on the productivity of farmers. Quality of services of the farmer’s cooperative has an influence in reaching the welfare of farmers, both directly and through the work productivity of farmers. The farmer’s cooperative should further improve its reliability by serving members on time. The farmers of the Subak of Sengempel should increase the labor productivity by increasing the quantity of labor, especially by increasing the number of main harvests. The Local Government through the relevant departments should further improve coaching, training and monitoring of the services of the farmer’s cooperative and improving agricultural extension programs. Keywords: service, productivity, farmers, welfare.